Two Quantitative Trait Loci Influence Whipworm (Trichuris trichiura) Infection in a Nepalese Population - Williams-Blangero, Sarah (2008)
BACKGROUND: Whipworm (Trichuris trichiura) is a soil-transmitted helminth which infects over a billion people. It is a serious public health problem in many developing countries and can result in deficits in growth and cognitive development. In a follow-up study of a significant heritability for whipworm infection, we conducted the first genome scan for susceptibility to this important parasitic disease. METHODS: We assessed whipworm eggs per gram of feces in 1253 members of the Jirel population of eastern Nepal. All sampled individuals belonged to a single pedigree containing over 26,000 relative pairs that are informative for genetic analysis. RESULTS: Linkage analysis of genome scan data generated for the pedigree provided unambiguous evidence for two quantitative trait loci influencing susceptibility to whipworm infection, one located on chromosome 9 (LOD = 3.35, genome-wide p = 0.0138) and the other located on chromosome 18 (LOD = 3.29, genome-wide p = 0.0159). There was also suggestive evidence for two loci located on chromosomes 12 and 13 influencing whipworm infection. CONCLUSION: The results of this first genome scan for susceptibility to whipworm infection may ultimately lead to the identification of novel targets for vaccine and drug development efforts.